Glucocorticoids Improve the Pregnancy Rate and Outcome in Women With Unexplained Positive Autoantibodies: A Systematic Review and Meta-Analysis - Li, Ting; Yuan, Yilin; Liu, Huixin; Lu, Qun; Mu, Rong (Frontiers in Medicine, 2022)
The effect of glucocorticoids (GCs) therapy for women with unexplained positive autoantibody is under debate. This systemic review and meta-analysis was performed to evaluate whether GCs administration can improve the pregnancy outcome of this population. Relevant publications were searched from databases and a total of 7 prospective and retrospective cohort studies which investigated effects of GCs administration in women with unexplained positive autoantibody were included. The outcomes of our systemic review and meta-analysis were measured in terms of risk ratio (RR) with 95% confidence intervals (CI) using fixed or random effect models. We found GCs treatment improved clinical pregnancy rate (RR 2.19, 95% CI 1.64 to 2.92) and live birth rate (RR 1.92, 95% CI 1.17 to 3.16), especially when started GCs administration before pregnancy (clinical pregnancy rate: RR 2.30, 95% CI 1.58 to 3.34; live birth rate: RR 2.30, 95% CI 1.58 to 3.34). However, no effect of GCs on miscarriage rate was found (RR 0.75, 95% CI 0.55 to 1.02) regardless of time of drug administration. Our systemic review and meta-analysis surports the rational use of GCs in women with unexplained positive autoantibody.